Continuum modeling of material interfaces and surfaces based on molecular statics computations. Issue 1 (21st October 2015) - Sievers, Christian; Mosler, Jörn
Abstract: The effective macroscopic properties of a broad variety of different materials are defined by the properties of the involved material interfaces and surfaces. However, in contrast to classical bulk materials, the mechanical properties of material interfaces can usually only be determined indirectly. For that purpose, two different approaches are presented which allow to compute macroscopic properties of material interfaces based on molecular statics computations. While the first of those is based on the principle of energy equivalence, the second one relies on the principle of stress equivalence. The advantages and disadvantages of both frameworks are analyzed. (© 2015 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)